1997
DOI: 10.1063/1.473909
|View full text |Cite
|
Sign up to set email alerts
|

Density functional study of polypropylene and its submolecules

Abstract: Articles you may be interested in Density functional theory study of self-association of N -methylformamide and its effect on intramolecular and intermolecular geometrical parameters and the cis/trans population A density functional study of crystalline acetic acid and its proton transfer polymorphic forms A density functional theory study of vibrational coupling between ribose and base rings of nucleic acids with ribosyl guanosine as a model system Previous density functional ͑DF͒ calculations of the structur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

1997
1997
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 29 publications
(21 reference statements)
1
11
0
Order By: Relevance
“…As a first step, we studied a decane molecule (C 10 H 22 ), which can be taken as representative of longer linear alkanes and, by extrapolation, of polyethylene. The equilibrium structural parameters, reported in Table 1, are in excellent agreement (within 1%) with other DFT results and with experimental data [24,25] for hydrocarbons and/or crystalline polyethylene (PE).…”
Section: Linear Alkanessupporting
confidence: 84%
“…As a first step, we studied a decane molecule (C 10 H 22 ), which can be taken as representative of longer linear alkanes and, by extrapolation, of polyethylene. The equilibrium structural parameters, reported in Table 1, are in excellent agreement (within 1%) with other DFT results and with experimental data [24,25] for hydrocarbons and/or crystalline polyethylene (PE).…”
Section: Linear Alkanessupporting
confidence: 84%
“…We optimize the atomic positions at fixed volume and shape of the unit cell by minimizing the forces on all atoms, following the method described in detail previously. 7,9 The electron-ion interaction is represented by ionic pseudopotentials with the ͑non-local͒ form suggested by Troullier and Martins. 20 We use s-nonlocality for the O atom.…”
Section: Methods Of Calculationmentioning
confidence: 99%
“…20 We use s-nonlocality for the O atom. Detailed tests of the convergence of the plane wave basis for small organic molecules 6 and PE 7 showed that reliable energy differences can be obtained using a kinetic energy cutoff of 30 a.u. for systems containing H and C, while 35 a.u.…”
Section: Methods Of Calculationmentioning
confidence: 99%
See 1 more Smart Citation
“…10,11 The electron-ion interaction is represented by ionic pseudopotentials with the ͑nonlocal͒ form suggested by Troullier and Martins. 12 We adopt periodic boundary conditions with a simple cubic cell with lattice constant 36 a.u.…”
Section: Methods Of Calculationmentioning
confidence: 99%